Penatalaksanaan Fisioterapi Pada Kasus Cervical Root Syndrome Di RST. Dr. Soedjono Magelang - Karsa Adi Nugraha, Yudhistira; , Sugiono S.Fis, MH.Kes (2015)
Background: Cervical Root Syndrome is a condition that is caused by irritation or cervical nerve root compression by disc protrusion invertebralis, the symptoms are neck pain that spreads to the shoulders, upper arm or forearm, parasthesia, and weakness or muscle spasm. One example of the disease is Syndrome radiculopathy. Radiculopathy means there is a pathological process in the posterior and anterior roots. Disorders that can be local or generalized. Root Cervical Syndrome have some symptoms that a sense of tense the neck, the presence of the neck pain radiating to the arms, especially the neck movement limitations encountered terjadang dizziness that can cause problems, given the modalities of this condition IR, TENS, Excercise Therapy. Objective: To determine the benefits of IR modalities, TENS and Excercise Therapy in reducing pain, improving LGS, and improve functional ability. Methods: The method used physiotherapy in the case that the modality IR, TENS, Excercise Therapy, and evaluation by using the VAS pain measurement methods, measurement and measurement LS with a midline neck pain increased activity with dissability Index. Results: After 6 times terpai showed a decrease in pain is pain silent: T1 0 - T6 0, Tenderness 4 T1 - T6 2, Pain motion: 7 T1 - T6 4 Conclusion: In the case of IR modalities, TENS and excercise therapy can reduce motion tenderness and pain, improve the LGS and improve functional ability